Parametric optimization of non-traditional machining processes using multi-criteria decision making techniques: literature review and future directions - Kalita, Kanak; Chakraborty, Santonab; Ghadai, Ranjan Kumar; Chakraborty, Shankar (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2023)
Continuous urge for generation of complex intricate features on harder and tougher materials with close dimensional tolerance and superior surface quality has led to the development of non-traditional machining (NTM) processes. Unlike the conventional machining processes, the NTM processes employ energy in various forms or their combinations for removal of material from the workpiece. As these processes are quite capital-intensive, their performance needs to be optimized. In this direction, applications of various multi-criteria decision making (MCDM) techniques have already become popular. This paper provides a comprehensive review of the present literature on the applications of MCDM techniques for parametric optimization of NTM processes. Among all the NTM processes, electrochemical machining (ECM), electrical discharge machining (EDM), wire electrical discharge machining (WEDM), abrasive water jet machining (AWJM), laser beam machining (LBM), ultrasonic machining (USM), and plasma arc machining (PAM) are considered in this paper due to their widespread acceptance in modern manufacturing industries. The essence of all the reviewed articles would help the process engineers in identifying the most suitable experimental design plan, work material, process parameters and responses, MCDM tools, criteria weight measurement techniques, and hybrid models for parametric optimization of NTM processes. Future directions are also included to explore the feasibility of newer MCDM tools to have more pragmatic solutions.